2012
DOI: 10.2527/jas.2012-5102
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality of swine supplemented with ractopamine under commercial conditions in Brazil1

Abstract: Commercial crossbred barrows and gilts (n = 340) were used to study the effects of different dietary inclusions of ractopamine hydrochloride (RAC) on quality of LM and semimembranosus muscle (SM). Pigs were blocked by BW (107.3 ± 0.76 kg) and allotted to gender-specific pens (10 to 12 pigs/pen), and within blocks, pens of barrows or gilts (10 pens/treatment) were randomly assigned to 1 of 3 dietary RAC inclusions (0, 5, or 10 mg/kg) fed during the last 28 d before slaughter. Initial (45-min) and ultimate (24-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 25 publications
12
23
0
1
Order By: Relevance
“…This result is in agreement with others (Fàbrega et al, 2010) who reported no immunocastration effect on muscle depth and Athayde et al (2012) who reported increases in muscle depth of pigs fed RAC diets.…”
Section: Carcass Traitssupporting
confidence: 93%
See 3 more Smart Citations
“…This result is in agreement with others (Fàbrega et al, 2010) who reported no immunocastration effect on muscle depth and Athayde et al (2012) who reported increases in muscle depth of pigs fed RAC diets.…”
Section: Carcass Traitssupporting
confidence: 93%
“…Rikard-Bell et al (2009) observed that the half carcass of immunocastrated males was heavier than those from intact males or animals fed RAC. Athayde et al (2012) also reported an increase in slaughter weight values, hot carcass and percentage of lean meat from pigs fed RAC in the diet. The favorable effect of immunocastration on lean meat percentage was also observed in several experiments: Moore et al (2009), Fàbrega et al (2010 and Braña et al (2013).…”
Section: Carcass Traitsmentioning
confidence: 82%
See 2 more Smart Citations
“…Leal et al (2014) (WARRISS et al, 1990;MØLLER;BERTELSEN;OLSEN, 1992;ZAGURY et al, 2002;STOLLER et al, 2003;APPLE et al, 2004;BRIDI et al, 2006;SILVEIRA et al, 2006;APPLE et al, 2008;FERNÁNDEZ-DUEÑAS et al, 2008;TONIETTI, 2008;PAULY et al, 2009;BETTS, 2011;ATHAYDE et al 2012;ŠKRLEP et al, 2012;CALDARA et. al., 2013).…”
Section: Vol_n_b1mentioning
confidence: 99%